2021
DOI: 10.2147/nss.s286131
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Transgender Identity, Sleep, Mental Health and Suicidality Among a North American Cohort of College Students

Abstract: The purpose of this study is to examine the associations between transgender identity, sleep, and mental health among a North American cohort of cisgender and transgender college students. Participants and Methods: This cross-sectional study surveyed 221,549 North American college students from the 2016-2017 American College Health Association-National College Health Assessment II. Bivariate and multivariable analysis examined associations among transgender identity and outcomes of insomnia symptoms, daytime s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Sleep may be a health disparity in sexual and gender minority individuals (i.e., lesbian, gay, bisexual, transgender, queer, or other identities) [34], and the potential mechanism underlying the observed sleep disparity is social and minority stress [16]. And social stress has a similar role regarding self-perceived and self-rated GNC.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep may be a health disparity in sexual and gender minority individuals (i.e., lesbian, gay, bisexual, transgender, queer, or other identities) [34], and the potential mechanism underlying the observed sleep disparity is social and minority stress [16]. And social stress has a similar role regarding self-perceived and self-rated GNC.…”
Section: Discussionmentioning
confidence: 99%
“…This study only differentiated between self-identified male and female medical students and does not specifically address symptoms or differences among students who identify as non-binary or gender nonconforming. Given the well-documented rates of MDD among this population in general, 39,40 it is worth exploring the specific effect of medical school exams on their mental health in future research. Additionally, we only surveyed students within a three-day period before and after exams, so we do not know what the lasting consequences of these symptoms are, or how long these symptoms truly exist both before and after exams.…”
Section: Limitationmentioning
confidence: 99%
“…Sleep quality was found to be an independent predictor of quality of life controlling for gender-affirming hormone therapy or gender-affirming surgeries ( Auer et al, 2017 ). Since the review by Butler et al (2020) was published, a large-scale study examining sleep, mental health, and suicide reported that transgender college students were more likely than cisgender students to experience inadequate sleep, daytime sleepiness, insomnia symptoms, and sleep disorder diagnosis ( Hershner et al, 2021 ). Additionally, an expanded report from a qualitative study of 40 gender minority people examined associations between sleep quality and mental health, and found that most participants endorsed some difficulties with sleep ( Harry-Hernandez et al, 2020 ).…”
Section: Sexual and Gender Minority People And Sleepmentioning
confidence: 99%
“…Regarding gender minority people, few studies have examined the association between sleep disturbance and STBs. In an analysis of data from the 2016–2017 American College Health Association National College Health Assessment II, transgender college students had higher rates of sleep disturbance including inadequate sleep, daytime sleepiness, insomnia symptoms, and a diagnosis of a sleep disorder as well as 3–4 times increase in the odds of reporting suicide ideation or suicide attempt ( Hershner et al, 2021 ). Although this study did not evaluate whether sleep disturbance functioned as a mechanism in the association between transgender identity and STBs, this study suggests that both sleep disturbance and STBs co-occur at high rates among gender minority people.…”
Section: Sleep Disturbance and Suicide-related Thoughts And Behaviors...mentioning
confidence: 99%